Perceptual learning style preferences of malay esl learners at tertiary level: A case study at UiTM Pahang / Badli Esham Ahmad - Ahmad, Badli Esham (Universiti Teknologi MARA Cawangan Pahang, 2007)
This study sets out to identify the perceptual learning style preferences of Malay ESL learners in Jengka Campus, UiTM Pahang. Data analysis from the study revealed that in general, Malay ESL learners in UiTM Pahang have major preferences for kinesthetic auditory individual and tactile learning styles. The present study also reveals that there are no statistical differences between the learning styles of both genders, and levels of achievement. This study has also revealed specific differences in learning styles according to fields of study and geographical backgrounds. A notable difference between rural and urban respondents is that the urban respondents have a major preference to visual learning while the rural respondents only displayed a minor preference for it. The other significant difference is that the rural respondents strongly preferred individual learning style, while the urban respondents only recorded a minor preference. East and West coast learners share similar preferences save for their different preference for visual learning style, which is considered as major for the West Coast and minor for the East Coast. The input according to fields of study, however, recorded some statistically significant differences between the faculties. However, they share almost identical learning style preferences, as they prefer kinesthetic and tactile as well as auditory.